Peripartum Cardiomyopathy: An Update (University Heart Journal, 2018)
Peripartum cardiomyopathy is a life threatening entity of peripartum period characterized by left entricular systolic dysfunction and heart failure in absence of any known cardiac disease. Though its incidence is rising but till now its incidence, pathogenesis, optimum management protocol are not known. Oxidative stress–prolactin hypothesis , anti-angiogenic-signalling excess hypothesis, viral myocarditis and genetic predisposition are some attractive etiologic explanation but nothing is proven comprehensively. Novel biomarkers and role of new imaging modalities are being investigated. As benefit by targeted therapy like bromocriptine or pentoxifylline are inconsistent, so controlling volume status, neutralizing maladaptive neurohormonal response and treatment of complications are required.prognosis is reasonably good. The aim of this review to highlight its pathophysiology, emerging investigatios modalities, and updated management protocol.University Heart Journal Vol. 14, No. 1, Jan 2018; 38-41